Global Magnetohydrodynamic Waves in Stably Stratified Rotating Layers - Márquez-Artavia, Xiomara (2017)
Márquez Artavia, X. (2017). Global magnetohydrodynamic waves in stably stratified rotating layers. (Tesis de Doctorado). The University of Leeds. Department of applied Mathematics.